2017
DOI: 10.1245/s10434-017-5820-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Waiting Time from Diagnosis to Treatment and Survival in Patients with Curable Gastric Cancer: A Population-Based Study in the Netherlands

Abstract: BackgroundIn the Netherlands, a maximum waiting time from diagnosis to treatment (WT) of 5 weeks is recommended for curative cancer treatment. This study aimed to evaluate the association between WT and overall survival (OS) in patients undergoing gastrectomy for cancer.MethodsThis nationwide study included data from patients diagnosed with curable gastric adenocarcinoma between 2005 and 2014 from the Netherlands Cancer Registry. Patients were divided into two groups: patients who received neoadjuvant therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 22 publications
6
42
0
Order By: Relevance
“…27 In addition, baseline waiting times were comparable with previously reported median waiting times of 4.6 weeks to the start of neoadjuvant treatment and 6 weeks to primary surgery. 28 Performing FDG-PET/ CT or SL was associated with a significantly prolonged waiting time from diagnosis to the start of treatment, both for neoadjuvant treatment (although clinically less relevant) and primary surgical treatment. Patients undergoing primary surgery are usually older and have several comorbidities, and are therefore not deemed fit enough for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, baseline waiting times were comparable with previously reported median waiting times of 4.6 weeks to the start of neoadjuvant treatment and 6 weeks to primary surgery. 28 Performing FDG-PET/ CT or SL was associated with a significantly prolonged waiting time from diagnosis to the start of treatment, both for neoadjuvant treatment (although clinically less relevant) and primary surgical treatment. Patients undergoing primary surgery are usually older and have several comorbidities, and are therefore not deemed fit enough for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing time to surgery up to greater than 8 weeks in the primary gastrectomy group did not impact overall survival. 60 Furukawa et al divided the time to surgery into three groups (30-60 days, 60-90, > 90). On initial univariate analysis, early surgery was associated with worse survival; however, after multivariate adjustment, time to surgery was not an independent prognostic factor for survival.…”
mentioning
confidence: 99%
“…They did not find a significant difference in mean length-of-stay. The implementation of a fast-track or ERAS program was also investigated as an addition to laparoscopic procedures [63][64][65]. A consecutive series of 32 patients showed that it was safe and had similar postoperative results [63].…”
Section: Eras and Fast-track Programsmentioning
confidence: 99%
“…The implementation of a fast-track or ERAS program was also investigated as an addition to laparoscopic procedures [63][64][65]. A consecutive series of 32 patients showed that it was safe and had similar postoperative results [63]. In addition, a randomized clinical trial in gastric cancer patients including 22 fast-track and 22 conventional care patients showed a shorter length of stay for fast-track patients (5 vs. 8 days, P<0.001) but no difference was noted for postoperative pain [64].…”
Section: Eras and Fast-track Programsmentioning
confidence: 99%
See 1 more Smart Citation